IDENTIFICATION OF CHARACTER VALUES LEVELS IN STUDENTS AT JUNIOR HIGH SCHOOL, JAMBI CITY - Nurmalia, Nia (Jurnal Kopendik, 2022)
The purpose of this study was to describe the level of character values ​​of grade VII students at SMP Negeri 17 Jambi City related to aspects of self-confidence, discipline, independence, communicativeness, and responsibility. The method in this study uses a quantitative research type using a descriptive approach. The results of this study indicate that the character values ​​of 7th grade students at SMP Negeri 17 Jambi City are in the "high" category with a percentage of 85.07%. The results of the analysis of item processing per-indicator obtained the results of the honest character value level with a percentage gain of 84.50%, the appreciation level with a percentage gain of 83.25%, the discipline character level with a percentage gain of 85.51%, the independent character level with a percentage gain of 80.28%, the level of communicative character of the percentage gain is 88.38%, the level of character is responsible for the acquisition of the percentage of 86.31% Keywords:. Identification, Character Values, Student Character